Developing Early Childhood Skills Through Project-Based Learning: A Study on the Implementation of the Merdeka Curriculum in Semarang, 2026 - Mursid Mursid; Husnul Hafidhoh; Muhamad Ansori; Mubarok Fatahillah (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah UI BBC, 2026)
This study is intended to assess the preparedness of PIAUD teachers in Semarang to implement the Merdeka Curriculum and embrace project-based learning (PBL) in early childhood education. The primary objective is to evaluate teachers' readiness to adopt the new curriculum, identify existing challenges, and examine the influence of PBL on student engagement and critical thinking. The research follows a qualitative descriptive approach, gathering data through semi-structured interviews, classroom observations, and document analysis involving 15 PIAUD teachers across five schools. Findings indicate that most teachers are moderately prepared to embrace the new curriculum, hampered by obstacles such as inadequate training, resource shortages, and resistance hindering effective PBL implementation. Despite these obstacles, teachers who effectively implemented PBL demonstrated increased student engagement and motivation. The study suggests targeted professional development and improved resource allocation are essential for the successful implementation of the Merdeka Curriculum and PBL. The study offers valuable insights for policymakers and educational administrators to support teachers in integrating innovative student-centered teaching practices into their instruction.